Peran Iklim Komunikasi dalam Mencapai Tujuan Organisasional di Universitas Atma Jaya Yogyakarta - Perbawaningsih, Yudi (FISIP Universitas Atma Jaya Yogyakarta, 2019)
Â Organization needs creativity that can be created by human resources to win the competition and achieve its goals. For higher education institutions, creativity is not only determined by the factors of lecturers and students, but also by external factors, namely the academic communication and creativity. This research used survey as the research method and the result shows that the organizational communication climate plays an important role in achieving organizational goals. For students, the communication climate influences the learning outcomes. For lecturers, the communication climate does not have direct influence in achieving organizational goals because of cultural factors.